PROFIL KINERJA GURU BIMBINGAN DAN KONSELING DALAM PENYUSUNAN PROGRAM PELAYANAN BIMBINGAN DAN KONSELING DI SMP NEGERI LINGGO SARI BAGANTI KABUPATEN PESISIR SELATAN - Yani, Iponofita; Kasih, Fitria; Nita, Rahma Wira (Bimbingan dan Konseling, 2013)
The problem of this research is how the application and counseling teacher profile in organizing the counseling teacher program guidance and counseling at SMP Negeri Linggo Sari Baganti. This research is caused by the counseling teacher who not make counseling planning program for semester or year. This research has purposes to describe the counseling teacher in organizing planning program at SMP Negeri Linggo Sari Baganti. This research is descriptive research. The population on of this research is the counseling teacher at SMP Negeri Linggo Sari Baganti who consist is counseling teacher because the population  100, so all of the population are used as sample by using total sampling. In collecting the data the researcher used a instrumentation is questioner and the data are analyzed by using presentation form. The finding of this research is the counseling  at SMP Negeri Linggo Sari Baganti, as follow: (1) The planning program of counseling have good criteria, (2) The activity of counseling have enough good criteria, (3)  In doing evaluation about the activity counseling teacher program have less good criteria, (4) In doing next step of the counseling program have less criteria. Based on the result of this research above the researcher suggests to the counseling teacher can keep  the process of organizing counseling planning and activity program that have good criteria, like the planning and activity program. In addition, the counseling teacher can more improve her the application  in doing 1) evaluation and 2) check again the counseling program, so the activity of counseling will run well in the future.